Optimizing HRM in Islamic Primary Schools: A Comparative Study in North Lampung - Sahayani B., Suri (Journal of Advanced Islamic Educational Management, 2025)
The recruitment, selection, and placement of competent human resources are critical for ensuring organizational effectiveness and achieving educational goals. This study analyzes the educator procurement systems at SDIT InsanRobbani and SDS Soekarno Hatta in North Lampung Regency. A descriptive qualitative approach was employed, collecting data through semi-structured interviews, participatory observation, and document analysis, followed by data reduction, presentation, and conclusion drawing, and validated through triangulation. Research participants included school principals, HR coordinators, and educators directly involved in staffing processes. The findings reveal distinct approaches: SDIT InsanRobbani applies a closed recruitment system relying on internal recommendations, whereas SDS Soekarno Hatta conducts open recruitment via official channels. Both schools implement selection stages including written tests, interviews, Qur’an recitation, and micro-teaching, but differ in administrative filtering—SDS rejects unqualified applicants, while SDIT shows more flexibility. Placement practices also contrast: SDIT bases assignments on commitment and one-month internship performance, while SDS evaluates candidates over a five-month internship before final placement. These differences reflect varying institutional philosophies, balancing trust, competence, and adherence to Islamic educational values. The study provides practical insights for optimizing HRM strategies in Islamic primary schools, demonstrating how recruitment and placement can align organizational goals with professional and moral standards.